Peran Orang Tua dalam Membimbing Fisik Fisiologis pada Anak Pendidikan Sekolah Dasar Rentang Usia 7-8 Tahun: Analisis Studi Literatur Review - Trisnani Widowati; Mia Hafizah Tumangger; Alfreeda Zaan Moira Dzulfikar; Elva Cinta Lamiis Susanto Putri; Taqiya Cantika As Salma; Ega Rahmania Putri; Nesha Ramadhani (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Physical motor development is an essential and easily observable indicator of children’s growth. Parental involvement plays a crucial role in optimizing this development, particularly during the child’s golden age. This study aims to analyze the importance of motor development and examine how parents support children’s learning through a developmental psychology perspective. Using a literature review method, the findings reveal that child development is shaped by genetic and environmental factors, while active support from parents and teachers has long-term effects on children’s physical, emotional, and social readiness. Understanding developmental psychology enables parents to provide appropriate stimulation that maximizes children’s potential. Using literature review methods, it was found that motor development is influenced by genetic and environmental factors, while positive interactions between children, parents, and educators contribute to long-term physical, social, and emotional development. A deep understanding of developmental psychology enables parents to design appropriate stimulation strategies to maximize their children's potential.